AN ASSESSMENT OF TEACHERS’ COPING MANAGEMENT OF PERCEIVED STRESS AND FEAR OF THE UNKNOWN - Merissa Braza Ocampo (Psikoislamedia : Jurnal Psikologi, 2020)
Amidst the burgeoning research currently conducted on the effects of COVID-19, this study looks particularly at teachers’ stress and anxiety during a time of heightened global uncertainty, which also strongly affects educational processes. The paper draws on data provided through online questionnaires, and follow-up interviews with teachers at a variety of educational institutions in Japan, the Philippines, and eight other countries. Findings from 100 respondents include details regarding the extent and distribution of various behaviors and emotional tendencies gained from quantitative analysis, and additional follow up questions, all conducted online. Numerous strategies for combatting the negative impact of COVID-19 are presented, and a variety of individual responses to this predicament is stressed. The study confirms that COVID-19 is having an unprecedented impact on education, affecting not only students but teachers as well. Thus, the study aims to both assist in alleviating the negative impacts on teachers’ wellbeing and to provide helpful insights that contribute to the body of knowledge on teachers’ coping management of perceived stress and anxiety.